2017
DOI: 10.1002/ppul.23755
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive high-frequency oscillatory ventilation versus nasal continuous positive airway pressure in preterm infants with moderate-severe respiratory distress syndrome: A preliminary report

Abstract: In this prospective, randomized controlled study, nHFOV significantly reduced the need for IMV as compared with nCPAP in preterm infants with moderate-severe RDS without increase in adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 23 publications
5
69
0
6
Order By: Relevance
“…In further steps towards implementation of non‐invasive mechanical ventilation, Zhu and colleagues report results from a randomized prospective trial comparing nCPAP and nHFOV for the treatment of patients with moderate to severe RDS who also received surfactant at diagnosis. The main outcome was the need for mechanical ventilation, which was higher in the nCPAP group.…”
Section: Neonatal Respiratory Distress Syndromementioning
confidence: 99%
“…In further steps towards implementation of non‐invasive mechanical ventilation, Zhu and colleagues report results from a randomized prospective trial comparing nCPAP and nHFOV for the treatment of patients with moderate to severe RDS who also received surfactant at diagnosis. The main outcome was the need for mechanical ventilation, which was higher in the nCPAP group.…”
Section: Neonatal Respiratory Distress Syndromementioning
confidence: 99%
“…Other recent studies have helped define the application of NIPPV to clinical care. Zhu et al performed a randomized, controlled trial of 81 infants with moderate to severe respiratory distress syndrome to either nCPAP or nHFOV . They determined that infants receiving nHFOV had a significantly lower need for invasive mechanical ventilation in this population, suggesting that nHFOV should be considered in the NICU to prevent the need for intubation.…”
Section: Introductionmentioning
confidence: 99%
“…While answers to the above‐mentioned questions will enhance our understanding of the promising data presented by Zhu et al we consider that important lessons can be learned from their study. First, the authors showed for the first time that nHFOV can be applied successfully to avoid invasive mechanical ventilation in the primary treatment of RDS.…”
mentioning
confidence: 96%
“…We appreciate the work by Zhu et al published in this journal, who presented the first prospective clinical study that investigated noninvasive high‐frequency oscillatory ventilation (nHFOV) in the primary treatment of preterm infants with respiratory distress syndrome (RDS). In a randomized controlled trial, they assigned 81 premature infants of 28‐34 weeks’ gestational age (GA) with moderate to severe RDS to receive either nHFOV or nasal continuous positive airway pressure (nCPAP) immediately after surfactant treatment.…”
mentioning
confidence: 99%